Bespoke Biomolecular Wires for Transmembrane Electron Transfer: Spontaneous Assembly of a Functionalized Multiheme Electron Conduit - Piper, Samuel E. H.; Edwards, Marcus J.; van Wonderen, Jessica H.; Casadevall, Carla; Martel, Anne; Jeuken, Lars J. C.; Reisner, Erwin; Clarke, Thomas A.; Butt, Julea N. (Frontiers in Microbiology, 2021)
Shewanella oneidensis exchanges electrons between cellular metabolism and external redox partners in a process that attracts much attention for production of green electricity (microbial fuel cells) and chemicals (microbial electrosynthesis). A critical component of this pathway is the outer membrane spanning MTR complex; a biomolecular wire formed of the MtrA, MtrB and MtrC proteins. MtrA and MtrC are decaheme cytochromes that form a chain of close-packed hemes to define an electron transfer pathway of 185 A. MtrA is wrapped inside MtrB for solubility across the outer membrane lipid bilayer; MtrC sits outside the cell for electron exchange with external redox partners. Here we demonstrate tight and spontaneous in vitro association of MtrAB with separately purified MtrC. The resulting complex is comparable to the MTR complex naturally assembled by Shewanella in terms of both its structure and rates of electron transfer across the lipid bilayer. Our findings reveal the potential for building bespoke electron conduits where MtrAB combines with chemically modified MtrC, in this case labeled with a Ru-dye that enables light-trigged electron injection into the MtrC heme chain.